SOSIALISASI PENGGUNAAN ANALISA.IO DALAM MENGANALISA AKUN SOSIAL MEDIA DI SMP PELITA II - Kalyani, Khema Dwi; Sharlene; Chintia, Tiffany; Yolanda, Aubrey; Geraldine, Karmelia; Mawardi, Viny Christanti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Social media has become a very significant medium on the internet, allowing users to represent themselves, interact, share and communicate virtually. In Indonesia, the growth of social media users is very fast, reaching 167 million users in 2023. Social media not only functions as an unlimited source of information and communication tool, but also plays a role in improving business skills and contributions. This research aims to spread awareness about the importance of understanding that social media can have positive and negative impacts, encouraging attention to wise use, especially for the younger generation. A social analytics platform, Analisa.io, uses artificial intelligence to help marketers, agencies, and influencers analyze public profiles and trends on social media. The seminar conducted by the writing team at SMP Pelita II aims to provide students with an understanding of the role of social media and how to analyze social media data. With its rapid growth and significant impact, this information needs to be conveyed to the younger generation. Therefore, the writing team carried out a bonus teaching assignment at SMP Pelita II, providing seminars and sharing insights about the effective and responsible use of social media with class 9C students.